Cross-sectional study of the rates of military sexual trauma (MST) and associations with adverse mental health outcomes among UK female ex-service personnel: a study protocol - Dominic Murphy; Nicola T Fear; Marie-Louise Sharp; Tamara Obradovic (BMJ Open)
Introduction This study investigates the rates of military sexual trauma (MST) and its associations with adverse mental health among a sample of UK female ex-service personnel who served during the Iraq/Afghanistan eras.Methods and analysis Female ex-service personnel, who participated in the fourth phase (Phase 4) of the King’s Centre for Military Health Research (KCMHR) Health and Well-being Cohort Study (2022–2023) and consented to be recontacted for follow-up studies (n=295), are being invited to participate in an online questionnaire between July 2024 and February 2025. The questionnaire contains surveys and questions related to experiences of sexual harassment and sexual assault during and outside of military service, disordered eating and broader female health issues. While the questionnaire relates to several female health topics, this study focuses on the surveys related to experiences of sexual trauma and eating disorders. Sociodemographic variables and some health variables, including post-traumatic stress disorder (PTSD), complex PTSD, common mental disorders, alcohol misuse, physical somatisation and social support, will be extracted from participants’ pre-existing data collected in Phase 4 of the KCMHR Cohort Study. Analyses will assess rates of MST, and hierarchical multiple logistic regressions will investigate associated health impacts. Rates and ORs, employing 95% CIs, will be reported.Ethics and dissemination This study has been granted full ethical approval by the King’s College London Research Ethics Committee (Ref: HR/DP-23/24–39040). Participants provide informed consent before participating and have access to a signposting booklet containing contact details for a range of support services. A risk protocol is in place, which outlines the procedure to be undertaken if a participant contacts the research team in distress. Findings will form part of a PhD thesis and will be further disseminated through peer-reviewed publication and dissemination with veteran mental health services and charities, and relevant government departments.